Analysis of Marketing Strategy for Coconut Brown Sugar Business as a Home Industry in Asahan Regency - Susi Tri Lestari*; Marliyah Marliyah (Universitas Syiah Kuala, 2023)
Coconut brown sugar has a role in the food industry, both at the home industry level to large-scale industry. The coconut brown sugar business, which is included in the household scale industry, is not immune from the constraints that occur in this business. These obstacles include marketing problems which sometimes result in unsold brown sugar products. However, this problem of unsold products rarely occurs. When many people are having celebrations, the demand for brown sugar will increase which results in producers sometimes have to refuse orders for brown sugar that are too much and exceed the amount of production each day. To make a business grow and have minimal problems, a strategy is needed to achieve a goal in the business. The purpose of this research is to analyze the marketing strategy carried out in the coconut brown sugar business in Binjai Serbangan Village. The research method used is descriptive qualitative with analysis techniques using the IFE matrix, EFE matrix, IE matrix, SWOT matrix, and QSPM matrix. Qualitative Strategic Planning Matrix is one of the most appropriate tools for making the necessary and effective priorities in preparing strategic plans. Based on the research conducted, it was found that the coconut brown sugar business is in the V quadrant